2011
DOI: 10.3390/cancers3010841
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Mediated Signaling in Pancreatic Pathogenesis

Abstract: Functionally, the pancreas consists of two types of tissues: exocrine and endocrine. Exocrine pancreatic disorders mainly involve acute and chronic pancreatitis. Acute pancreatitis typically is benign, while chronic pancreatitis is considered a risk factor for developing pancreatic cancer. Pancreatic carcinoma is the fourth leading cause of cancer related deaths worldwide. Most pancreatic cancers develop in the exocrine tissues. Endocrine pancreatic tumors are more uncommon, and typically are less aggressive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 158 publications
1
17
1
5
Order By: Relevance
“…In contrast, the expression levels of MMP-2 and MMP-9 were significantly induced by FGF-2 treatment. It has been reported that many patients with pancreatic cancer overexpress FGF-2, which leads to the activation of the ERK1/2 pathway, increased expression of MMPs and higher invasive potential (9)(10)(11). In addition, in the present study, TIMP-1 levels did not change after celecoxib treatment, suggesting that a different pathway is involved in the regulation of TIMP-1 expression in PANC-1 cells.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In contrast, the expression levels of MMP-2 and MMP-9 were significantly induced by FGF-2 treatment. It has been reported that many patients with pancreatic cancer overexpress FGF-2, which leads to the activation of the ERK1/2 pathway, increased expression of MMPs and higher invasive potential (9)(10)(11). In addition, in the present study, TIMP-1 levels did not change after celecoxib treatment, suggesting that a different pathway is involved in the regulation of TIMP-1 expression in PANC-1 cells.…”
Section: Discussioncontrasting
confidence: 44%
“…It is overexpressed in PDAC (9), and the FGF-2 receptor has been reported to correlate with tumor metastasis, stage and retroperitoneal invasion (10). In addition, low expression of FGF-2 has been associated with longer post-operative survival in PDAC patients (11). In general, FGF-2 can exerts its biological effects by binding to FGFR-2, which leads to the activation of a number of signaling cascades; in which the most dominant is the MAPK/ERK pathway (12).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Li et al [27] found that serum VEGF level and VEGF content within the pancreatic tissue were increased early in AP, and the highest level was found after 12 h of inducing AP. On the other hand, Nandy and Mukhopadhyay [29] mentioned that up-regulation of the VEGF/VEGF receptor system is limited to malignant transformation of the pancreas and is not associated with pancreatitis. In an attempt to explain the mechanism of Mel and VEGF interaction, Silva et al [39] postulated that Mel may be involved in the regulation of neoangiogenesis due to its modulatory role in immunity and haematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning PDGF receptors, high PDGFRb expression was found to be correlated with poor disease-free survival in pancreatic cancer and additionally colon and ovarian cancer patients [35]. Overall, growth factors and their receptors have been shown to result in progression and metastasis formation of pancreatic cancer and engagement of factors such as VEGF and PDGF and their signaling cascades appear to be crucial for the progression of this devastating disease [36]. …”
Section: Discussionmentioning
confidence: 99%